In-depth investigation of turn-around time of full blood count tests requested from a clinical haematology outpatient department in Cape Town, South Africa - Leonard Mutema; Zivanai Chapanduka; Fungai Musaigwa; Nomusa Mashigo (African Journal of Laboratory Medicine, 2021)
Background: The performance of laboratories can be objectively assessed using the overall turn-around time (TAT). However, TAT is defined differently by the laboratory and clinicians; therefore, it is important to determine the contribution of all the different components making up the laboratory test cycle.